Global access to existing and future antimicrobials and diagnostics: antimicrobial subscription and pooled procurement. Issue 2 (February 2022) - Berman, Daniel; Chandy, Sujith J; Cansdell, Oliver; Moodley, Krishnee; Veeraraghavan, Balaji; Essack, Sabiha Y
Summary: The COVID-19 pandemic has underlined the importance of an efficient and equitable supply of and access to essential health products. These factors are equally pertinent to the antimicrobial resistance pandemic, in which access to a portfolio of existing and pipeline antimicrobials plus complementary diagnostics is crucial. This Viewpoint focuses on market shaping in low-income and middle-income countries (LMICs), where the need for effective antimicrobials and complementary diagnostics is most acute. We propose the creation of a subscription and pooled procurement model that consolidates the growing demand for a portfolio of antimicrobials and diagnostics in LMICs. Anchored by regional market leaders, these pooling mechanisms would guarantee consistent private-sector and public-sector access in participating countries, while creating conditions for long-term best practice in stewardship. Supported by data from South Africa and India, this proposal sets out an innovative approach to tackle the antimicrobial resistance crisis in LMICs.